Structural and Morphological Characterization of Zeolite X Synthesized from Sodium Silicate via a Microwave-Assisted Sol–Gel Method for Detergent Applications - Oktavia Eka Ardyanti; Yuca Salzadilla Basori; Sintha Soraya Santi; Reva Edra Nugraha (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
X-zeolite is a faujasite-type zeolite widely applied in detergents. Its high ion-exchange capacity, organized pore structure, and environmentally friendly nature make it highly valuable. This study aims to synthesize Zeolite X using a microwave-assisted sol-gel method. Sodium silicate (Na2SiO3) and aluminium hydroxide (Al(OH)3) serve as precursors. We determined optimal synthesis conditions using the Taguchi L25(53) method with the following variables: molar ratio of SiO2/Al2O3 (1-1.5), crystallisation time (5-25 min), and microwave power (120-700 W). Optimal conditions included a SiO2/Al2O3 ratio of 1.375, a crystallisation time of 5 min, and a microwave power of 250 W. Power consumption was 0.0208 kWh, and yield was 37.93%. FT-IR analysis showed characteristic absorption bands at 1011 cm-1 (Si-O-Si), 781 cm-1 (T-O-T), and 565 cm-1 (D6R ring). The XRD pattern displayed a faujasite phase with 83.90% crystallinity. SEM images revealed slightly irregular octahedral crystals, averaging about 8 ?m. These results suggest the method is economical and can produce Zeolite X for phosphate-free detergent formulations. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and Production